Limnological monitoring of the river San Francisco –RJ as a tool of environmental management for companies which use it as a source of water resources - Esteves, Rafael Alves; Rocha, Jorge Roberto da Silva Lima (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The limnological monitoring is an important environmental management tool because it represents the quality of water that will be used throughout the manufacturing process, including the disposal of effluent. This paper aims to present the limnological monitoring as key instrument in making decisions of corporate environmental issues. The interfaces of the limnological monitoring and the positive impacts were discussed, both for business and for society, generated by the process of implementing an environmental monitoring program. The object of this study was the San Francisco River in the Rio de Janeiro state, as well as all industrial hub that use the river as a source of water resources. The reality is local, however the environmental theme of the discussion can be widely applied to all freshwater ecosystems where there are companies using limnologic environments as a source of water resources. Special attention was given to environmental education, a key to the implementation of any contemporary environmental activity. Social, economic, environmental, legal and cultural aspects make up the set of interfaces which the limnological assessment relates.